Graphic news : how sensational images transformed nineteenth-century journalism - Frisken, Amanda (Urbana : University of Illinois Press, 2020)
""You furnish the pictures and I'll furnish the war." This famous but apocryphal quote, long attributed to newspaper magnate William Randolph Hearst, encapsulates fears of the lengths to which news companies would go to exploit visual journalism in the late nineteenth century. From 1870 to 1900, newspapers disrupted conventional reporting methods with sensationalized line drawings. A fierce hunger for profits motivated the shift to emotion-driven, visual content. But the new approach, while popular, often targeted, and further marginalized, vulnerable groups. The author examines the ways sensational images of pivotal cultural events-obscenity litigation, anti-Chinese bloodshed, the Ghost Dance, lynching, and domestic violence-changed the public's consumption of the news. Using intersectional analysis, Frisken explores how these newfound visualizations of events during episodes of social and political controversy allowed newspapers and social activists alike to communicate-or challenge-prevailing understandings of racial, class, and gender identities and cultural power"--
Introduction: Sensationalism and the Rise of Visual Journalism -- "We Simply Illustrate": Sensationalizing Crime in the 1870s "Sporting" News -- "Language More Effective than Words": Opium Den Illustrations and Anti-Chinese Violence in the 1880s -- "A First-Class Attraction on Any Stage": Dramatizing the Ghost Dance and the Massacre at Wounded Knee -- "A Song without Words": Anti-Lynching Imagery as Visual Protest in the 1890s Black Press -- "Wanted to Save Her Honor": Sensationalizing the Provocation Defense in the Mid-1890s -- Epilogue: Legacies of Visual Journalism and the Sensational Style.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Journalism, Pictorial -- United States -- History -- 19th century; Sensationalism in journalism -- United States -- History -- 19th century; Presse illustrée -- États-Unis -- Histoire -- 19e siècle.; Sensationnalisme journalistique -- États-Unis -- Histoire -- 19e siècle.; LANGUAGE ARTS & DISCIPLINES -- General; Journalism, Pictorial; Sensationalism in journalism; United States; 1800-1899; Electronic books; History